2012
DOI: 10.3389/fneur.2012.00030
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Animal Models for Studies on the Mechanisms of Blast-Induced Neurotrauma

Abstract: A blast injury is a complex type of physical trauma resulting from the detonation of explosive compounds and has become an important issue due to the use of improvised explosive devices (IED) in current military conflicts. Blast-induced neurotrauma (BINT) is a major concern in contemporary military medicine and includes a variety of injuries that range from mild to lethal. Extreme forces and their complex propagation characterize BINT. Modern body protection and the development of armored military vehicles can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 89 publications
1
77
1
Order By: Relevance
“…Similarly, endothelial damage results in a loss of tight junction integrity and consequently the potential for increased blood-brain barrier permeability and microvascular injury (Duckworth et al, 2012). Notably, increased BBB permeability has been found as late as one month following blastinduced brain injury in a preclinical rodent model, indicating the presence of lasting microvascular dysfunction (Rubovitch et al, 2011). Furthermore, blast-induced BBB disruption has been observed to occur more extensively on the contralateral side, as well as at fluid-tissue interfaces such as that surrounding the lateral ventricles (Readnower et al, 2010), consistent with the findings reported within this study in which the contralateral side was more severely injured in comparison to the ipsilateral side based on standard markers of neural degeneration, astrocyte reactivity, and microglial activation (Garman et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, endothelial damage results in a loss of tight junction integrity and consequently the potential for increased blood-brain barrier permeability and microvascular injury (Duckworth et al, 2012). Notably, increased BBB permeability has been found as late as one month following blastinduced brain injury in a preclinical rodent model, indicating the presence of lasting microvascular dysfunction (Rubovitch et al, 2011). Furthermore, blast-induced BBB disruption has been observed to occur more extensively on the contralateral side, as well as at fluid-tissue interfaces such as that surrounding the lateral ventricles (Readnower et al, 2010), consistent with the findings reported within this study in which the contralateral side was more severely injured in comparison to the ipsilateral side based on standard markers of neural degeneration, astrocyte reactivity, and microglial activation (Garman et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…The scaling equations developed have displayed significant utility in the development of injury risk functions based upon the high level of agreement with pre-existing experimental data concerning blast survival and injury risk. As such, while scaling of blast injury and associated blast parameters based on subject weight has not been related to neural injury (Park et al, 2011), scaling represents a logical step forward in more closely replicating clinically relevant exposures in laboratory models Rafaels et al, 2012;Risling and Davidsson, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such accumulations have been reported in blast and are generally attributed to rotational acceleration rather than to primary blast. 46,75 However, effects by smoke emission and heating (quaternary blast) cannot be excluded. Gene expression in the hippocampus has been shown to be very different in this model for primary blast, compared with rotational injury.…”
Section: Tbi and Monoamine Turnovermentioning
confidence: 99%
“…One method for generating overpressures representative of actual explosions is the use of gas-driven overpressure shock tubes Chavko et al 2008;Desmoulin and Dionne 2009;Gorbunov et al 2008;Long et al 2009;Risling and Davidsson 2012;Sundaramurthy et al 2012;Svetlov et al 2010). Although blast shock tube models are state-of-the-art for investigation of the mechanisms related to blastinduced TBI, there are some limitations to their use.…”
Section: Introductionmentioning
confidence: 99%